BJHP – Building on our strengths - Alison Wearden; David French (British Journal of Health Psychology, 2013)
OBJECTIVE: Premature ovarian insufficiency (POI) and early menopause (EM) can have life-altering physical and psychological impacts, with potential consequences for an individual's sense of self. However, understanding of these potential consequences is limited, with much of the literature generalizing such experiences from naturally occurring menopause. This scoping review aimed to increase understanding around the alteration of self-concept in adults, presumed female at birth, diagnosed with POI or EM. METHODS: In line with the Joanna Briggs Institute (JBI) protocol for scoping reviews, database searches were conducted, with eligible studies consisting of peer-reviewed literature exploring how self-concept and/or its associated constructs are impacted by POI or EM. RESULTS: Database searches identified 473 manuscripts, with 35 full-text manuscripts reviewed and 12 deemed to be eligible for inclusion. Impacts to physical, social and emotional self-concept were indicated across studies, and detailed via content analysis. Contextual factors were suggested to greatly influence the extent of self-concept impact. The impact of spontaneous versus medically induced POI and/or EM on self-concept showed some variation; however, detailed explanation for this was limited across the manuscripts. CONCLUSION: This review provides greater understanding of the disruptive nature of POI or EM, potentially impacting all aspects of self-concept-physical, social and emotional. Such outcomes emphasize the importance of recognizing the unique experiences of POI and EM and the need for individualized understanding and care. Further research is needed to better understand the experiences of these individuals and their support and treatment needs.